1970
DOI: 10.3171/jns.1970.33.5.0574
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue reaction to some chronically implanted metals

Abstract: ✓ The toxicity of certain metals, namely, platinum, platinum-8% tungsten, platinum-10% rhodium, platinum-10% iridium, platinum-10% nickel, platinized platinum, a gold-nickel-chromium alloy, a gold-palladium-rhodium alloy, a chromium-nickel-molybdenum alloy (Vitallium), stainless steel, silver, rhenium, and gold, was evaluated histologically following chronic implantation for 2 months in the brains of cats. Of the above metals, all but silver were found to be nontoxic. Boron was also evaluated and found to be n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(52 citation statements)
references
References 12 publications
1
48
0
1
Order By: Relevance
“…An in vitro study of five types of polyimide demonstrated that these materials do not elicit any cytotoxic response, and induce little haemolysis and only a moderate degree of coagulation (97-98% of normal for Kapton™) making polyimides an attractive candidate as biosensor encapsulants [37]. Platinum, a noble metal, is generally reported as nontoxic [38] while the medical grade cyano-acrylate glue (Loctite, 4011) also complies with the Loctite ISO-10 993 Biocompatibility test program.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study of five types of polyimide demonstrated that these materials do not elicit any cytotoxic response, and induce little haemolysis and only a moderate degree of coagulation (97-98% of normal for Kapton™) making polyimides an attractive candidate as biosensor encapsulants [37]. Platinum, a noble metal, is generally reported as nontoxic [38] while the medical grade cyano-acrylate glue (Loctite, 4011) also complies with the Loctite ISO-10 993 Biocompatibility test program.…”
Section: Discussionmentioning
confidence: 99%
“…Since they are in direct contact with tissues, the biocompatibility of the MEAs is necessary. Metal based MEAs such as gold, platinum and iridium as well as polymer-based MEAs are considered non-toxic and are widely used in neural interface devices [11][12][13][14][15]. Promising results have also been obtained from optical transparent materials such as indium tin oxide (ITO) electrodes [16,17].…”
Section: Introductionmentioning
confidence: 92%
“…The platinum and iridium alloy composition of the contacts is common for stimulation electrodes because it has a high Warburg capacitance (thus low electrode-tissue capacitance), low allergenicity, and reportedly minor tissue capsule formation compared with many other materials such as copper and steel. 9,13 Reactions to platinum and iridium have been reported, largely limited to industrial workers with chronic exposure in recycling centers processing catalytic converters. 1,5,12 Testing should include evaluation for immediate and delayed hypersensitivity through skin prick and patch testing, respectively.…”
Section: Discussionmentioning
confidence: 99%